ETIKA BISNIS SAYYID HADRAMI DI DAERAH KHUSUS IBU KOTA JAKARTA (STUDI PT. NILAM WIDURI DAN PT. DAR AL-KUTUB AL-ISLAMIYAH) - Habib Muhammad (Institut Agama Islam Sahid Bogor, 2023)
This study aims to analyze the business ethics of the sayyid hadhrami in the Special Capital Region of Jakarta by taking two companies, namely PT. Patchouli Widuri and PT. Dar Al-Kutub Al-Islamiyah. The Hadhrami sayyid community in this area are mostly traders of perfumes and Arabic-language books. The interesting thing is that they have inherited Islamic business ethics from generation to generation until today. The research method used in this research is normative-qualitative in which data is obtained through observation, interviews and studies on documents related to the research object. Data analysis uses the norms of business ethics in Islam with the validity of the data through triangulation. The conclusion of this study is that the business carried out by the syayid hadhrami community in DKI Jakarta is developing quite well. This can be seen in the various fields of business carried out by this community. Two of them are PT. Nilam Widuri and PT. Dar al-Kutub Al-Islamiyah whose owner is a Syayid. The business ethics implemented by the two companies are aligned with Islamic business ethics as reflected in the characteristics of the Prophet Muhammad, namely; siddiq, amanah, fathanah, and tabligh. This can be seen in maintaining product quality and good relations which are the implementation of the characteristics of Shiddiq, Fathanah (Itqan) and Tabligh. Finally, the two companies also believe that the existence of blessings is the goal of the Company as an implementation of the nature of trust. Belief in the existence of blessings in business which is a goal other than worldly profits.